Analisis Kinerja Distribusi Tempe UMKM Menggunakan Discrete Event Simulation: Studi Kasus Indragiri Hulu - Yelita Anggiane Iskandar; Ahmad Faisal Dahlan; Nanda Ruswandi; Syathirastra Sakhiyllani Rachman; Indriani Syafira; Army Wahyu Ramadhani; Fyinkha Vanessia Lumban Tobing (Jurnal Ilmiah Teknik Informatika (TEKINFO), 2026)
The tempeh distribution system in micro, small, and medium enterprises (MSMEs) often facesimbalances in internal process capacity, leading to increased waiting times and order backlogs.This study aims to model and analyze the performance of the tempeh distribution system inIndragiri Hulu Regency using a Discrete Event Simulation (DES) approach. The simulation modelwas developed using ProModel software to represent the operational flow of order receiving,packaging, inspection, and delivery processes based on actual operating conditions. The analysiswas conducted using a baseline scenario and one proposed improvement scenario, withperformance indicators including location utilization, waiting time, and work in process (WIP).The simulation results indicate that in the baseline scenario a bottleneck occurs at the packagingprocess, characterized by a very high level of location utilization. The proposed scenario reducesthe workload pressure on the packaging stage and improves the distribution of system workload,although capacity utilization in the inspection and delivery stages remains relatively low. Thesefindings demonstrate that the DES approach is effective for identifying system bottlenecks andevaluating improvement alternatives in MSME-scale tempeh distribution systems.